PENGARUH DISIPLIN KERJA DAN KEMAMPUAN KERJA TERHADAP PENILAIAN KINERJA PEGAWAI ADMINISTRASI UMUM DI SATUAN POLISI PAMONG PRAJA PROVSU MEDAN - Silaban, Ernawati; Marbun, Fretty romauli; Gaol, Jonner Lumban; Tarigan, Jenni (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2024)
Performance evaluation is a structured and unbiased assessment process of employees' job performance within a company, with the primary aim of furnishing employees with feedback on their performance for the purpose of aiding in their career development. The objective of this study is to ascertain the influence of work ethics and work proficiency on the assessment of employee performance, both individually and collectively. The approach used to gather data for this research employs a Likert scale and a survey questionnaire. The technique applied for data analysis encompasses descriptive analysis, Multiple Linear Regression Statistics, Research Data Analysis, Classical Assumption Test, and Hypothesis Test. This investigation employed random sampling, which is a method of selecting samples at random from the population under examination. The study's total population was 650 individuals, with a sample size of 87 people selected using the slovin formula. The analytical tool used is Statistical Product and Service Solutions (SPSS) 22. The analysis outcomes reveal that work ethics (X1) exert a significant and positive impact on employee performance evaluation at the Pamong Praja Police Unit Provsu Medan. This is evidenced by the computed t-value (3.770), surpassing the tabulated t-value (1.6627), and with a significance level less than 0.05 (0.000 < 0.05). Moreover, work proficiency demonstrates a substantial and favorable influence on employee performance evaluation at the Pamong Praja Police Unit Provsu Medan. This is demonstrated by the calculated t-value (2.472), exceeding the tabulated t-value (1.6627), with a significance level lower than 0.05 (0.015 < 0.05). When taken together, work ethics and work proficiency exhibit a noteworthy and constructive effect on employee performance evaluation, substantiated by the computed F-value (142.086) exceeding the tabulated F-value (3.107), and a significance level of 0.000 below 0.05. The coefficient of determination (R2) test results demonstrate that work ethics and work proficiency can elucidate 22.3% of the variability in employee performance evaluation, while other factors contribute to the remaining portion.